IMPLEMENTASI KEBIJAKAN GREEN GROWTH KOREA SELATAN - Ari Putra; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the implementation of green growth policy of South Korea. Concept of green growth is a new paradigm in economic development that discussed in international organizations such as UNEP (United Nation Environment Program) and OECD (Organization Economy Cooperation Development). South Korea is a country with high consumption in energy and one of the most highest GHG emissions country. The green growth policy of South Korea is a way to improves independence energy and mitigating climate change.This research is using descriptive and library research methods. The data and information obtained from books, journals, and websites. This research uses neo-realism and security non traditional theory to explain why South Korea uses green growth as its national policy.The result of this research shows that South Korea starts to develop clean energy and uses green technology in efficiency energy consumption and reduce its GHG emissions. By using the five-year plan in green growth policy, the government invests about 2 percent of its GDP in Research and Development (R & D) of clean energy and green technology.government and private sectors starts to expand its industries in green technology and uses clean energy.Keyword :South Korea, green growth, independence energy, mitigating climate change